Commentary: The Transgender Child: A Lesson in Acceptance (LEARNing Landscapes, 2014)
In this interview, 12-year-old Wren Kauffman shares his earliest memories of "not feel[ing] right" in his body and how he conveyed this powerful sentiment to his parents. Wren and his mother Wendy discuss the transgender journey their family has gone on, which initially started by contacting the Institute for Sexual Minority Studies and Services at the University of Alberta. Wren recounts how he told friends and classmates that he was transgender, talks about the support and openness he has received from teachers, friends, and schools, and of the critical importance of acceptance. Issues such as bullying, gender-neutral spaces, and diversity are also discussed. In addition, Wendy emphasizes the key role education plays in the inclusion of transgender children: "If we can start from a place of education, and explain that there is a really wide kind of variety of different ways that people can be born, that’s going to help society and people in general understand that transgender people are in the world."
Keywords: interview; transgender; gender neutral space; bullying; school